AN ANALYSIS OF CODE SWITCHING OF HOUSEKEEPING TEACHER’S TALKS OF “ILHAM CRUISE SHIP TRAINING CENTER MAGELANG” BATCH 16 - May Willyana; Dwi Winarsih; Rini Estiyowati Ikaningrum (Faculty of Education and Teachers Training, 2018)
Housekeeping is brand new material that the students have never had before. The language that is used to deliver the material is English, but it is English for Specific Purpose which designed to meet specific needs of the learners. So, there are a lot of new terms that the students hear for the first time. Moreover, the students have different capability in acquiring the material. The students sometimes cannot understand the material and it leads to a boring classroom situation. Besides, the students’ lack of vocabulary and the teacher still finds difficulties in choosing the right words to explain the materials. In this case, switching language used in classroom with the language that the students easily understand helps a lot. Code switching has various types and functions, and they are very useful. The objectives of the study are to know what types and functions of code switching used by the housekeeping teacher’s talks of “Ilham Cruise Ship Training Center Magelang” batch 16. This is a descriptive qualitative research that focuses on the Housekeeping teacher’s talks as the subject. The writer deals with the documentation of the teaching learning activities which obtained on November 6th until November 22nd 2017. The data collection is started by observing, taking notes, recording, and interviewing the teacher about his purpose of using code-switching in the classroom interaction.The findings show that there are two types of code switching based on Wardhaugh’s theory (2015), namely Situational switching and Metaphorical switching. Meanwhile, there are six functions of code switching according to Sampson (2012). They are code switching as equivalence function as metalanguage function as floor holding function), as reiteration function as socializing function and as L2 avoidance function.